Performance Evaluation of a Microcontroller-Based 350 W BLDC Motor Control System - Duwi Hariyanto; Muhammad Dianra Amani Ihsan; Basril Amien Mana; Dahril Khudni; Rudi Uswarman; Dean Corio; Nia Saputri Utami; Indarta Kuncoro Aji (Journal of Energy, Material, and Instrumentation Technology, 2026)
Electric vehicles are increasingly adopted as a strategic solution for reducing carbon emissions, yet their overall performance is strongly influenced by reliability, responsiveness, and energy efficiency. This study presents a performance evaluation of a microcontroller-based speed-control system for a 350 W brushless DC (BLDC) motor, developed using low-cost components with potential for local manufacturing. The proposed system incorporates a throttle input, Pulse Width Modulation (PWM) for speed regulation, three Hall-effect sensors for rotor position feedback, and an Arduino Nano controller integrated with an IR2110 driver and a three-phase HY4008 MOSFET inverter. A series of subsystem level tests, covering the power supply, control units, signal amplification, sensing, and motor operation, were conducted under no-load and loaded conditions using a 250 W generator as the mechanical load. The results indicate that the power supply remained stable within 50.5 50.7 V, and the IR2110 effectively amplified the 5.119 V PWM signal to 10.41 11.47 V. Hall sensor frequency increased from 129 Hz at 30% throttle to 179 Hz at 100% throttle, reflecting improved commutation synchronization with rising rotor speed. The motor achieved a speed increase of 90.8% from 220.7 rpm to 421.2 rpm under no-load, whereas under load it increased from 137.8 rpm to 356.4 rpm (an increase of 158.6%). These findings confirm that increasing the PWM duty cycle enhances electromagnetic torque and maintains rotor-stator synchronization across varying load conditions. The study demonstrates that a low-side PWM strategy with six-step commutation can be effectively implemented using low-cost hardware, supporting domestic innovation in electric vehicle technology and contributing to sustainable, low-emission transportation development.